Child Wellbeing during COVID-19: A Cross-sectional Study from Pakistan - Fatima Shafiq; Shelina Bhamani; Komal Abdul Rahim; Mohsina Gujrati; Amir Raza; Lumaan Sheikh (ziauddin University, 2024)
Background: The closure of schools because of the physical restrictions applied by the government has only amplified the hardships on children, parents, and teachers alike. Thus, this study aimed to assess parents' perception of the impact of COVID on their young children.   Methods: A cross-sectional survey was taken from the parents(n=128) parents of children ages 3-8 years, using a self-reported questionnaire. A tailored-made questionnaire google link was sent to the parents registered for the webinar.  The link had all the details pertinent to the ethical considerations for the use of data. SPSS was used andp˂0.05 was considered statistically significant.   Results: In total, 128 participants responded to the link sent to them via email and 122(95.3%) parents feared (high and medium) of sending their children back to the schools and out of which 110(85.9%) of them reported that they are confident in preparing their kids for the new everyday routine. Almost 75% of parents shared that the overall routine of the children is disturbed (directly or indirectly), and the children have started eating unhealthy food. Moreover, 51.6% (66/128) parents reported that mental issues (such as aggression and anxiety) have significantly (p=0.027) risen amongst the children, and 39% (50/128) showed that learning has been negatively affected. Consequently, the children's physical activity has significantly reduced, they get bored while staying at home and are not learning new things.   Conclusion: There is a need to raise awareness about the detrimental impacts of the pandemic on early childhood development, learning, and wellness.   Keywords: COVID-19; Children; Parents; Wellbeing.